Canicross Pilot Programme: Basic Considerations for Its Implementation as an Extracurricular Sports Activity - Xabier Gonzalez-Santamaria; Erika Borrajo; Eneko Sanchez-Mencia; Maite Aurrekoetxea-Casaus (MDPI AG, 2024)
Canicross is a sport that consists of running while being pulled by a dog in a natural environment. Due to the benefits to health and well-being that it brings to the people and dogs that practise it, this sport could be implemented as an animal-assisted intervention (AAI) in the educational field. Against this background, the present work describes a pilot experience carried out in an educational centre in the Basque Country for the implementation of canicross as an extracurricular sports activity. The main objective is to describe the educational potential of canicross as an extracurricular activity that fosters students' values of respect for animals and physical activity (PA) in natural environments. The results of this innovative experience provide the first evidence of the valuable role of animal activities in this educational context, where current academic research is practically non-existent. In conclusion, we highlight the novelty of the proposal and the motivating effect that the dogs in this case had among the students in encouraging them to practise PA and adhere to values of respect and animal welfare.